Japan in the Early Modern World: Religion, Translation, and Transnational Relations - Triplett, Katja; Orii, Yoshimi; Jolliffe, Pia Maria (Übersetzungskulturen der Frühen Neuzeit, 2025)
Contributors -- Conventions -- 1 Introduction: Japan in the Early Modern World – Religion, Translation, and Transnational Relations -- I. Reconsidering Language and Materiality in Missionary Translation -- 2. Revisiting Native Agency: Cultural and Material Translations of Christianity in Early Modern Japan -- 3. From Nanbanjin to Kabukimono: Portraying Iberians in Early Modern Japan -- 4. Translating European Punctuation into Japanese: Investigating the Printing of the Sanctos no gosagueô (Acts of the Saints) -- 5. To Wish and to Pray in Jesuit Japanese Grammars -- II. Translocational Books and Their Histories -- 6. Translatio of the Sanctos no gosagueô (Acts of the Saints, 1591) Published by the Jesuit Mission Press in Japan: An Overlooked Copy in the Bibliothèque Nationale de France -- 7. Bridging Religion, State, and Asian Trade in the Seventeenth Century: John Evans and the Bodleian Japanese Jesuit Missionary Print of 1596 -- 8. Early European Owners of Jesuit Prints and Manuscripts from Japan: A View Based Chiefly on Book Sale Catalogues -- III. Crossing Legal, Political, and Denominational Boundaries -- 9. Women in Repudiation and Divorce Cases in the Christian Mission: Jesuit Translation Strategies and Normativities in Sixteenth- and Seventeenth-Century Japan -- 10. Cultural Translations and Editorial Processes: A Study of the Translated Jesuit Texts Linked to the Japanese Mission Included in The Principal Navigations (Vol. 2, 1599) by R. Hakluyt -- 11. ‘This Iaponian Palme-tree of Christian Fortitude’ – Jesuit Letters From Japan in Early Modern England -- IV. Appendix -- 12. A Hand-List of Prints from the Jesuit Mission Press in Japan and Related Materials -- Japanese and Chinese Terms and Titles of Historical Works.